Improving rice productivity and profitability through efficient use of nitrogen and phosphorus fertilizers : Fertilizer source effects on rice growth and yield - Ferdous, Jannatul; Akter, Gufrana; Hoque, Md Anamul; Hoque, Tahsina Sharmin (Annals of Bangladesh Agriculture, 2026)
Nitrogen (N) and phosphorus (P) are essential for rice production, and diammonium phosphate (DAP), which supplies both N and P may provide agronomic and environmental advantages relative to urea. We evaluated seven fertilization strategies in BRRI dhan49: control (T₁), urea at N rate but no P (T₂), DAP at the N rate (T₃), urea at N rate + TSP at P rate (T₄), DAP at the P rate (T₅), no N and no P (T₆), and DAP at P rate + urea at N rate (T₇). Treatments were assessed for growth, yield, nutrient uptake, and post-harvest soil fertility. Fertilization significantly affected all parameters. T₇ produced the highest plant height (94.7 cm) and grain yield (5.65 t ha⁻¹), followed by T₄ (93.9 cm; 5.12 t ha⁻¹). Relative to the control, T₇ increased grain yield by 41% and total plant N uptake by ~75%, and it delivered the highest values for key yield components (panicle length, tillers hill⁻¹, and filled grains panicle⁻¹). Post-harvest soils under T₇ and T₄ showed elevated organic C, total N, and available P, indicating improved fertility. Profitability analysis identified T₇ as the most lucrative fertilized option (net return 5.08 × 10⁶ Tk ha⁻¹) and T₅ as the most cost-efficient (BCR 3,825) due to minimal input cost. Collectively, a regimen combining basal DAP with split urea applications enhances yield, nutrient uptake, and soil fertility while maintaining strong economic performance in BRRI dhan49. Ann. Bangladesh Agric. 29(2): 157-174